2019
DOI: 10.1142/s0217984919503032
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review on the variants of support vector machines

Abstract: Machine learning (ML) represents the automated extraction of models (or patterns) from data. All ML techniques start with data. These data describe the desired relationship between the ML model inputs and outputs, the latter of which may be implicit for unsupervised approaches. Equivalently, these data encode the requirements we wish to be embodied in our ML model. Thereafter, the model selection comes in action, to select an efficient ML model. In this paper, we have focused on various ML models which are the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…This is an indicator of the fact that SVM works well for such problems where the data-sets are relatively small. SVM is a binary linear classifier that maps feature points in space, creating different categories [ 83 ]. These categories are separated by a gap as wide as possible.…”
Section: Resultsmentioning
confidence: 99%
“…This is an indicator of the fact that SVM works well for such problems where the data-sets are relatively small. SVM is a binary linear classifier that maps feature points in space, creating different categories [ 83 ]. These categories are separated by a gap as wide as possible.…”
Section: Resultsmentioning
confidence: 99%
“…SVM is a type of classifier that performs binary classification on samples by supervised learning. [21,22] Its goal is to obtain the hyperplane with maximum margin to separate the samples. Compared with the other classification algorithms, the overall dependence of SVM on training samples is small.…”
Section: Establishment Of Svm Model Based On Principal Componentsmentioning
confidence: 99%
“…A hinge loss function for margin maximization along with a regularization parameter makes the SVM a robust classifier. A good review about variants of SVM can be found in [98].…”
Section: ) Support Vector Machinesmentioning
confidence: 99%